A comparative study of endoscopic combined intrarenal surgery (ECIRS) in the galdakao-modified supine valdivia (GMSV) position and minimally invasive percutaneous nephrolithotomy for complex nephrolithiasis: a retrospective single-center study - Zhao, Fangzhou; Li, Jun; Tang, Lei; Li, Chunming (Urolithiasis, 2021)
The aim of this research is to compare the efficiency and safety between endoscopic combined intrarenal surgery (ECIRS) in the Galdakao-modified Supine Valdivia (GMSV) position and minimally invasive percutaneous nephrolithotomy (Mini-PCNL) in a single session for the treatment of complex nephrolithiasis. 140 consecutive patients who were diagnosed with multiple pyelocaliceal stones or staghorn renal calculi were enrolled and reviewed retrospectively. Demographic, clinical information and surgical outcomes were collected and analyzed. Demographic variables and stone characteristics did not show statistically differences. Over 80% of the patients were diagnosed with multiple pyelocaliceal stones, while the remainders were branched renal calculi. Over half of the patients were classified into medium and high Seoul National University Renal Stone Complexity scoring system (S-ReSC) score groups. The stone free rate (SFR) in the single session was significantly higher in the ECIRS group than in the Mini-PCNL group (88.06% vs. 66.67%, P = 0.003). The subgroup analysis revealed that ECIRS was more efficacious than Mini-PCNL for complex renal calculi with medium and high S-ReSC scores ( P = 0.002). A nonsignificant but relatively lower postoperative complication rate was noted in the ECIRS group (7.5 vs. 16.0%, P = 0.12). With the exception of postoperative hospitalization days ( P < 0.001), significant difference was not detected between the two groups for other procedure-related information. ECIRS in the GMSV position is an effective and safe treatment especially for medium and severe complex nephrolithiasis, with significant higher SFR in the single session and relatively low procedure-associated morbidity compared to Mini-PCNL.